HTML5 for IOS and Android : a beginner's guide - Nixon, Robin, 1961- (San Francisco, Calif. : McGraw-Hill Osborne Media, 2011)
"A step-by-step tutorial to HTML5 mobile application developmentHTML5 for iOS and Android: A Beginners Guide leads you from the first steps of creating a Web page, through styling it with CSS, and then giving it dynamic interactivity with JavaScript. You'll learn how to create real-world websites and apps for both the Apple iPhone/iPad and Google Android platforms. Advice on how to handle platforms such as Nokia, Palm Pre, and others is included. The book serves as a one-stop guide and reference, providing all the information required to develop useable mobile apps and websites from scratch. Features covered include offline support, Canvas, video, advanced forms, and the Geolocation API.HTML5 for iOS and Android: A Beginners Guide Provides an all-in-one guide for mobile developers--everything needed to go from beginner status to pro developer is included Explains both basic HTML and HTML5 Covers Apple iPhone/iPad and Google Android platforms Shows how to create websites, web apps, and self-contained (native) apps Contains a full JavaScript tutorial, with particular reference to using it on mobile and touch devices Includes a guide to using CSS in a mobile environment Features detailed graphics for every step of each process Offers the examples from the book for download Easy-to-follow coverage: The Core Technologies; Introduction to HTML; What's New in HTML 5; Introduction to CSS; The CSS3 Enhancements; Introduction to JavaScript; Using JavaScript with HTML5; Introduction to PHP; Introduction to MySQL; Developing for Mobile Devices; Developing Mobile Friendly Websites; Using the eML eBook Platform; Developing Web Applications; Creating Self-Contained Applications; Setting Up the Apple SDK; Creating iOS Standalone Apps; Setting Up the Android SDK; Creating Android Standalone Apps"--
Machine generated contents note: Part I: The Core Technologies -- Chapter 1 Introduction to HTML -- Chapter 2 What's New in HTML 5 -- Chapter 3 Introduction to CSS -- Chapter 4 The CSS3 Enhancements -- Chapter 5 Introduction to JavaScript -- Chapter 6 Using JavaScript with HTML5 -- Chapter 7 Introduction to PHP -- Chapter 8 Introduction to MySQL -- Part II: Developing for Mobile Devices -- Chapter 9 Developing Mobile Friendly Websites -- Chapter 10 Using the eML eBook Platform -- Chapter 11 Developing Web Application -- Part III: Creating Self-Contained Applications -- Chapter 12 Setting Up the Apple SDK -- Chapter 13 Creating iOS Standalone Apps -- Chapter 14 Setting Up the Android SDK -- Chapter 15 Creating Android Standalone Apps.
Includes bibliographical references and index.
Keywords: Android (Electronic resource); HTML (Document markup language); Smartphones -- Programming; iOS (Electronic resource); Computers / Internet / Application Development